Digital Nomads as A Strategy to Accelerate the Religious Tourism Recovery in Post-Pandemic - Shofi'unnafi, Shofi'unnafi; Kusuma, Bayu Mitra A. (IJIBE (International Journal of Islamic Business Ethics), 2023)
This study aims to analyze the potential of Kudus Regency in implementing digital nomads as a strategy to accelerate Islamic religious tourism recovery after the COVID-19 pandemic. This research is important because even though pandemic control has gotten better, there is no guarantee that a virulent virus like COVID-19 will not emerge again and then have an impact on the tourism vacuum. To examine the potential of digital nomads in the Kudus Regency, the research results will be displayed using four aspects of tourism products including attraction, accessibility, amenity, and ancillary, and then discussed with SWOT as an analytical tool. This study uses a qualitative and descriptive approach where data collection is done by observation, interviews with seven informants, and focus group discussions with ten experts. The research results showed that: First, the attraction aspect is very promising because of the many and a varied number of Islamic religious tourism destinations in Kudus. Second, the accessibility aspect still needs improvement because the bus is the only mass public transportation option that directly reaches Kudus. Third, the amenities aspect requires adjustments to prices and health protocol standards. Fourth, the ancillary aspect is quite promising because health facilities, banking, and internet networks are wellavailable. Thus, attraction and ancillary become elements of strength (S), accessibility becomes weakness (W), and amenities become opportunity (O). However, attraction can also turn into a threat (T) if it is not managed properly because many tourist objects have died after the pandemic.